Relationship of HbA1c to Diabetic Retinopathy in Type 2 DM Patients at Haji Adam Malik General Hospital 2017-2018 - Silalahi, Yuni; Ricke Loesnihari (Talenta Publisher, 2020)
Diabetic retinopathy is a microvascular complication of diabetes mellitus. This complication can occur due to hyperglycemia that occurs in blood vessels for a long period of time. To determine whether there is a relationship between HbA1c levels on the incidence of diabetic retinopathy on pationts with type 2 diabetes mellitus in Haji Adam Malik General Hospital Medan period of 2017 until 2018. This research is an analitical study with retrospective method (case control) and conducted at the General Hospital of Haji Adam Malik Medan. Data collection was performed on medical records of diabetic retinopathy patients at Haji Adam Malik General Hospital Medan in the period January 2017 to December 2018. Data were collected by using medial records of patients with simple random sampling technique with a total sample is 46 samples, 23 samples of diabetic retinopathy, and 23 samples that were not diabetic retinopathy. The results of this study indicate that of 23 diabetic retinopathy samples, 2 of them had controlled HbA1c and the other 21 are not controlled. As well as of the 23 samples were not diabetic retinopathy, 5 of them had HbA1c controlled HbA1c and 18 were uncontrolled. The result of the analysis with chi square test showed no relationship between HbA1c levels to the incidemce of diabetic retinopathy in Type 2 DM patients with a p value of 0,06. From this study it was found that there was no relationship between HbA1c levels and the incidence of diabetic retinopathy for Haji Adam Malik General Hospital in the 2017-2018 period.